The Influence Of Brand Image, Product Innovation, And Word Of Mouth On Purchase Decisions For Ms Glow In Batam - Mayleni; Nur Elfi Husda (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
In the industrial era, there are many skincare companies that pay attention to current developments in producing products for sale. Each company has its own characteristics to attract consumer attention. Competition in the field of entrepreneurship is also increasingly diverse, there are more and more entrepreneurs in various industrial fields. In this research, we analyze the brand image of the Ms Glow product, in this competition the company must improve the product brand image so that the brand becomes the best, product innovation that influences sales of the Ms Glow product to innovate the Ms Glow product into a good product, and consumers will provide information from mouth to mouth. word of mouth to provide information from consumers to other consumers due to the use of the product. In this research, multiple linear regression analysis method was used. Based on the test results using the multiple linear regression analysis method with the help of SPSS 25, the results showed that brand image, product innovation and word of mouth had a significant effect on purchasing decisions.In the industrial era, there are many skincare companies that pay attention to current developments in producing products for sale. Each company has its own characteristics to attract consumer attention. Competition in the field of entrepreneurship is also increasingly diverse, there are more and more entrepreneurs in various industrial fields. In this research, we analyze the brand image of the Ms Glow product, in this competition the company must improve the product brand image so that the brand becomes the best, product innovation that influences sales of the Ms Glow product to innovate the Ms Glow product into a good product, and consumers will provide information from mouth to mouth. word of mouth to provide information from consumers to other consumers due to the use of the product. In this research, multiple linear regression analysis method was used. Based on the test results using the multiple linear regression analysis method with the help of SPSS 25, the results showed that brand image, product innovation and word of mouth had a significant effect on purchasing decisions.